Small angle neutron scattering study of a gehlenite-based ceramic fabricated from industrial waste - Chee, Wah Loy; Matori, Khamirul Amin; Zainuddin, Norhazlin; Whitten, Andrew E.; Campo, Liliana de; Md Nasir, Nur Izzah; Baharuddin Pallan, Nur Fadilah; Mohd Zaid, Mohd Hafiz; Alassan, Zarifah; Schmid, Siegbert (Trans Tech Publication, 2019)
This paper presents a small angle neutron scattering (SANS) study of a novel porous gehlenite-based ceramic, synthesised from a homogeneous powder mixture of soda-lime-silicate (SLS) glass, α-alumina, calcite and calcium fluoride via solid-state sintering at 1200 °C. The products of sintering at single temperatures from 600 to 1200 °C are examined by X-ray diffraction (XRD). Sintering of the mixture below 1200 °C forms two intermediate phases (Na₂ CaSi₃ O₈ and Ca₄ Si₂ O₇ F₂ ). Nepheline and α-alumina are minor phases in the gehlenite-based ceramic fabricated through sintering at 1200 °C. The microstructure of the gehlenite-based ceramic is investigated using field-emission scanning electron microscopy (FESEM) and SANS at the Australian Centre for Neutron Scattering. This study also evaluated the specific surface area of the gehlenite-based ceramic (~3.0 m² cm⁻ ³) from quantitative analysis of SANS data.